A comparison of one versus two appointment endodontic therapy in dogs' teeth with apical periodontitis - Holland, Roberto [UNESP]; Otoboni Filho, José Arlindo [UNESP]; Souza, Valdir de [UNESP]; Nery, Mauro Juvenal [UNESP]; Bernabé, Pedro Felício Estrada [UNESP]; Dezan Junior, Eloi [UNESP] (Lippincott Williams & Wilkins, 2003)
This study was conducted to observe the healing process in dogs' teeth with apical periodontitis after root canal treatment in one or two appointments. Premolars and anterior dogs' teeth had their root canals opened to the oral environment for 6 months before being treated. After root canal negotiation they were filled by the lateral condensation technique with gutta-percha points and Sealapex in one appointment or after a dressing with calcium hydroxide for 7 and 15 days. Six months after the treatment the animals were killed and the tissues prepared for histomorphological analysis. Scores attributed to the different histomorphological events were submitted to statistical analysis, which resulted in ranking the experimental groups from the best to the worst in the following way: (a) calcium hydroxide 14 days; (b) calcium hydroxide 7 days; and (c) one appointment. It was concluded that the use of a calcium hydroxide dressing helps to achieve better results (p < 0.01) than the treatment in one appointment.